2021
DOI: 10.1021/acsapm.1c00840
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Flexible Strain Sensors Based on Conductive Fillers and Thermoplastic Polyurethane Matrixes

Abstract: Over recent years, flexible strain sensors have been playing an increasingly important role, especially in wearable electronics, healthcare equipment, electronic skins (e-skins), and soft robots. Numerous materials are utilized in these applications; however, thermoplastic polyurethane (TPU) is prominently used for its elastomer-like behavior, suitable flexibility, and facility of combination with diverse conductive materials. These characteristics satisfy the growing demands for better stretchability, higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 113 publications
(395 reference statements)
1
38
0
Order By: Relevance
“…The crude was recrystallized from ethanol to obtain a white powder as the final product (Yield: 16.5 g, 62%). 1 (2). Compound 2 was synthesized using a previously published protocol with slight modifications as described below: 1 (10 g, 55.4 mmol) in 100 mL of anhydrous DCM was taken into a two-necked flask, TEA (22.9 mL, 165.0 mmol) was added, and this mixture was stirred for 30 min under a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude was recrystallized from ethanol to obtain a white powder as the final product (Yield: 16.5 g, 62%). 1 (2). Compound 2 was synthesized using a previously published protocol with slight modifications as described below: 1 (10 g, 55.4 mmol) in 100 mL of anhydrous DCM was taken into a two-necked flask, TEA (22.9 mL, 165.0 mmol) was added, and this mixture was stirred for 30 min under a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Thermoplastic polyurethane (TPU) is an attractive material with many key features such as ease of fabrication, low cost, excellent processability, transparency, and favorable chemical and solvent stability. Due to these remarkable features, TPU is used in many industrial sectors such as automobiles, footwear, wires, cables, coatings, etc. TPU has a low LOI of 19%, low thermal stability, and poor flame retardancy and shows melt dripping, which limits its use in various areas that require fire safety. , Therefore, it is essential to enhance the fire performance of TPU by adding a flame retardant (FR). The incorporation of a small amount of flame retardant additive (which hinders the propagation of the combustion process either by terminating the active H • and OH • radicals or by forming a char layer limiting the expansion of fire after ignition) has been shown to improve the flame retardancy of TPU significantly. …”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes and graphene are often grown by chemical vapor deposition (CVD) and then prepared by curing with a flexible substrate. It is worth noting that scholars often use the method of adding conductive fillers to improve conductivity. Therefore, the content and state of conductive fillers dispersed in the matrix have a significant impact on the conductivity of the sensor. , In addition to the blending method, the dispersion solution infiltration method ,,, and the spraying method are also widely used by scholars. These avoid the difficulty of uniformly dispersing conductive fillers in the elastic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…There are various categories in nano additives based on their nature, such as carbonaceous, 11–13 silicate‐based nanoparticles, 14,15 and their hybrid systems 16 . One of the most applicable additives among the named particles is carbon nanotubes (CNTs), which have attracted a great deal of attention due to their strong microwave absorptivity alongside their excellent mechanical, thermal, and electrical properties 16–18 . Paton et al 19 demonstrated the efficiency of CNTs as microwave absorbers by measuring the heating rate of the CNTs being dispersed in silicone oil as a transparent matrix.…”
Section: Introductionmentioning
confidence: 99%
“…16 One of the most applicable additives among the named particles is carbon nanotubes (CNTs), which have attracted a great deal of attention due to their strong microwave absorptivity alongside their excellent mechanical, thermal, and electrical properties. [16][17][18] Paton et al 19 demonstrated the efficiency of CNTs as microwave absorbers by measuring the heating rate of the CNTs being dispersed in silicone oil as a transparent matrix. They found that by incorporating just 0.04 wt% CNTs, the microwave absorbance of the silicone oil increased by five 100-fold.…”
Section: Introductionmentioning
confidence: 99%